Propiedades antirradicales libres y antibacterianas de extractos de corteza de pino - Rosales Castro, Martha; Pérez López, María Elena; Ponce Rodríguez, María del Carmen (Instituto de Ecología, A.C., 2016)
Free radicals scavengers of ethanolic and aqueous extracts from Pinus ayacahuite, Pinus cooperi, Pinus durangensis, Pinus leiophylla and Pinus teocote bark were evaluated, using the diphenylpicrylhydrazyl (DPPH) radical assay, to extract concentrations of (250, 500, 750, 1000 and 1250) mg L-1. The scavengers were compared with butilhydroxitolueno (BHT) and butilhydroxianisol (BHA) . Ethanolic extracts had higher activity than the aqueous one, specially P. leiophylla and P. durangensis, with scavengers at500 mg L-1 of (90,4 ± 0,98) % and (83,0 ± 1,41) %, similar to BHA (83,6 ± 0,20) % and higher than BHT (50,3 ± 0,72) %. Other than P. cooperi all extracts showed scavengers higher to 90,0 % at 1250 mg L-1. The concentration for scavengers 50,0 % of radical (CE50)  was evaluated. The antimicrobial activity of the extracts was evaluated using agar dilution method against Staphylococcus aureus, Enterococcus sp., Escherichia coli and Pseudomonas aeruginosa to concentrations of (0,625, 2,5, 5,0, 10,0 and 20,0) mg/mL. The minimal inhibitory concentration (MIC)  was reported. Ethanolic extracts had higher activity than the aqueous one. S. aureus was the most inhibited (MIC 0,625 mg/mL), Enterococcus sp. moderaty inhibited (MIC 2,5 mg/mL), E. coli do not had a good inhibition (MIC 10,0 to 20,0) mg/mL. P. aeruginosa only was efficiently inhibited by P. cooperi (2,5 mg/mL) ethanolic extract.